2019
DOI: 10.3390/jcm8081254
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease in HIV Infection

Abstract: Antiretroviral therapy (ART) has significantly improved life expectancy of infected subjects, generating a new epidemiological setting of people aging withHuman Immunodeficiency Virus (HIV). People living with HIV (PLWH), having longer life expectancy, now face several age-related conditions as well as side effects of long-term exposure of ART. Chronic kidney disease (CKD) is a common comorbidity in this population. CKD is a relentlessly progressive disease that may evolve toward end-stage renal disease (ESRD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 120 publications
(137 reference statements)
4
37
4
1
Order By: Relevance
“…This phenomenon can not be explained explicitly thus far. 32 A speculation of far from mature is that TDF, as a wellknown nephrotoxic antiretroviral, causes a rapid stress in renal tubular at the beginning exposure followed by a transient recovery possibly from the self-repairing mechanisms of kidney; then, an inevitable damage occurs if beyond the ability of self repairment over time. 33 Among TDF users, during the increasing period (1.40-2.30 years) of eGFR, the incidences of both outcomes, especially RKFD definitely declined (suggesting a recovery of renal function), even though TDF continued.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can not be explained explicitly thus far. 32 A speculation of far from mature is that TDF, as a wellknown nephrotoxic antiretroviral, causes a rapid stress in renal tubular at the beginning exposure followed by a transient recovery possibly from the self-repairing mechanisms of kidney; then, an inevitable damage occurs if beyond the ability of self repairment over time. 33 Among TDF users, during the increasing period (1.40-2.30 years) of eGFR, the incidences of both outcomes, especially RKFD definitely declined (suggesting a recovery of renal function), even though TDF continued.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney transplantation in HIV‐infected patients is nowadays a safe and effective treatment of end‐stage renal disease 1,2 . The success of kidney transplantation in the HIV population is principally based on the control of HIV replication and the reduction of the host immune response 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Although these drugs usually undergo several clinical trials before they are declared safe, several reports have indicated that they could possess nephrotoxic properties [4]. The kidney plays a major role in the excretion of antiretroviral drugs and this makes it vulnerable to various types of injuries from some of these agents including Acute Kidney Injury (AKI), tubulopathies, Chronic Kidney Disease (CKD) and end stage renal disease requiring renal replacement therapy [5]. Antiretroviral therapy can contribute to renal dysfunction directly by inducing acute tubular necrosis, acute interstitial nephritis, crystal nephropathy, and renal tubular disorders or indirectly via drug interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy can contribute to renal dysfunction directly by inducing acute tubular necrosis, acute interstitial nephritis, crystal nephropathy, and renal tubular disorders or indirectly via drug interactions. [5] Chronic kidney disease should be diagnosed in its early stages through routine screening and careful attention to changes in glomerular filtration rate or creatinine clearance [6]. It is also important that patients with Chronic Kidney Disease (CKD) are not denied the best combi- nations, especially since most drugs can be adjusted based on the estimated glomerular filtration rate [7].…”
Section: Introductionmentioning
confidence: 99%